TINGKAT PENDAPATAN PETERNAK TERHADAP KOMODITAS UNGGULAN PETERNAKAN AYAM RAS PEDAGING DI KABUPATEN TABANAN - Ni Luh Putu Inten Rumini; I Gede Ketut Sri Budarsa (STIMI Handayani Denpasar, 2012)
Agribusiness is one unit of activities that deals with a sequence chains of production, yield processing, and marketing that correlated with agriculture in a wide sense. Thepoultry business is one kind of agribusiness which are commercially profitable. Thisresearch goal is to know the contribution of income rates and work to economic levelof chicken breeder in Tabanan regency. Research result shows chicken livestock inTabanan regency have a significant contribution to the income of chicken breeder.Majority of chicken breeder make a chicken livestock as a main job, this is shown by35 respondents from 50 respondents or 70% are make a chicken livestock as a mainjob, and 15 respondents or 30% make a chicken livestock only as a secondary jobnot as a main job.From 50 respondents, the average amount of chickens from one livestock are3,170 chickens for one respondents. The average income of chicken breeder is Rp327.524.375, maintenance cost Rp 273.482.130 with the profit Rp 54.042.245 peryear. Therefore one way to increase income level for the breeder is help and lend themmoney for initial capital with low rate and uncomplicated birocration. This Ï€can bedone by Bank Pembangunan Daerah (BPD) and Koperasi Unit Desa (KUD).